Evaluating the use of functionally graded materials inserts produced by selective laser melting on the injection moulding of plastics parts - Beal, V. E. (2007)
The demand for productivity and shape complexity on the injection moulding industry necessitates new research to improve tool design, material, and manufacturing. A research field is the development of functionally graded materials (FGMs) to build injection moulds. For example, moulds built with the FGMs technique can have distinctive regions with higher heat conduction. Higher rates of heat transfers from thicker regions of the injected part can be useful to produce better and cheaper injection moulded polymer parts. It is possible to obtain moulds with differential conductivity by adding locally, during the fabrication of the mould, copper to the mould base material such as tool steel. In this work, an investigation into the effect of FGM copper (Cu)-tool steel mould insert over polymer injected parts is presented. The work is divided in two parts: a numerical thermal analysis comparison between Cu-tool steel graded and tool steel inserts and an injection moulding experiment with comparisons between mould surface temperature and degree of crystallinity of polypropylene parts. The numerical model was used to compare different behaviour of the mould heat transfer according to the mould insert material. Thereafter, a bolster was built to hold FGMs and tool steel inserts obtained by a selective laser fusion process. Polypropylene was injected over the inserts to compare with the numeric results. To observe the effect of the cooling rate in the polypropylene parts using the graded inserts, the degree of crystallinity of the parts was measured by differential scanning calorimetry (DSC) test. The temperature of the mould was also evaluated during the injection cycles. The results showed that the graded Cu-tool steel inserts tested had lower capacity to store heat energy. As Cu was added to the tool steel, the mixture proved to transfer heat more efficiently but it had less capacity to absorb heat.